2006
DOI: 10.1073/pnas.0509307103
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans cells cross-present antigen derived from skin

Abstract: cross-presentation ͉ dendritic cells ͉ epidermis ͉ mouse or murine ͉ epicutaneous

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
149
2
10

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(172 citation statements)
references
References 47 publications
11
149
2
10
Order By: Relevance
“…Murine myeloid DCs cross-present viral antigens and induce anti-viral CD8 1 T cells [37]. Murine LCs were reported to cross-present antigens [14] although a role for Langerin 1 dermal DCs was not excluded. More recently, in vivo studies indicate that murine Langerin 1 dermal DCs, but not LCs, are responsible for the induction of CD8 1 T-cell responses [38,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Murine myeloid DCs cross-present viral antigens and induce anti-viral CD8 1 T cells [37]. Murine LCs were reported to cross-present antigens [14] although a role for Langerin 1 dermal DCs was not excluded. More recently, in vivo studies indicate that murine Langerin 1 dermal DCs, but not LCs, are responsible for the induction of CD8 1 T-cell responses [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…However, the ability of LCs to cross-present exogenous antigens to CD8 1 T cells has been debated [14][15][16][17]. Klechevsky et al [13] have shown that in vitrogenerated human LCs from either CD34 1 cells or monocytes are capable of cross-presenting influenza-virus proteins to CD8 1 T cells.…”
mentioning
confidence: 99%
“…Indeed, they have been shown to take up skin Ags and migrate to the skin draining lymph nodes (2) where they can potentially interact with T cells. Based primarily on in vitro studies, it is envisaged that LCs undergo a process of maturation coordinate with migration, where they upregulate MHC, costimulatory, and adhesion molecules, and act as potent stimulators of naive CD4 and CD8 T cells when they arrive in the lymph node (3)(4)(5). Indeed, epicutaneous immunization strategies, which are presumed to involve LC, are effective at inducing functional CTL (6,7) and have led to clinical trials with positive preliminary findings for influenza and travelers' diarrhea (www.iomai.com) (8,9).…”
mentioning
confidence: 99%
“…We reported recently that Langerhans cells isolated from epidermis or emigrated from skin explants cross-presented soluble protein or cell-associated antigen on MHC-class I molecules to CD8 + T cells. Activated CD8 + T cells produced IFN-upon restimulation and exerted cytotoxic activity [53].…”
Section: Langerhans Cell Functions Relevant To Cancer Immunotherapy: mentioning
confidence: 99%
“…We demonstrated recently that Langerhans cells capture exogenous skin-derived antigen, process it and cross-present antigenic peptides on MHC-class I to CD8 + T cells in vitro and in vivo [53]. Langerhans cells thus represent a major subset of skin dendritic cells that, together with dermal dendritic cells, are equipped to fulWll the task of surveying skin for invading pathogens and stimulating immune responses against skin-borne pathogens [43].…”
Section: Functions Of Langerhans Cellsmentioning
confidence: 99%